Penerapan Metode Problem Based Learning dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Akidah Akhlak Kelas X di MAN 3 Tambakberas Jombang - Nur Inayah; Khoirul Umam (YASIN, 2026)
Although various learning innovations have been developed, the use of conventional learning methods in the Akidah Akhlak subject remains dominant and is still less capable of improving students’ activeness and learning outcomes. This study aims to analyze the implementation of the Problem Based Learning (PBL) method in improving the learning outcomes of tenth-grade students at MAN 3 Jombang. This study employed a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation involving subject teachers and tenth-grade students as the research subjects. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the implementation of PBL was carried out through the stages of planning, implementation, and evaluation. This method was able to increase students’ activeness, enthusiasm, and understanding of the learning materials, which ultimately had an impact on improving learning outcomes. These findings affirm that PBL is effective in supporting Akidah Akhlak learning that is more active and meaningful. The implications of this study indicate the importance of the teacher’s role as a facilitator in managing learning and creating a conducive learning environment so that the implementation of PBL runs optimally.